Bi-LSTM Neural Network for EEG-based detection of musical characteristics - Ariza Cervera, Isaac; Guillén, Sergio; Tardón-García, Lorenzo José; Barbancho-Pérez, Ana María; Barbancho-Pérez, Isabel (My University, 2023)
Electroencephalography (EEG) combined with Deep Learning and digital signal processing allows for mental activity recognition. In our study, a new feature extraction model-based is presented when combined with Bi-LSTM Neural Networks for EEG musical characteristics classification. This method can be used for both intra- and inter-subject scenarios reaching compelling accuracy values.
Keywords: Redes neuronales (Informática); Aprendizaje; Música - Estudio y enseñanza; EEG; BI-LSTM; Musical characteristics; Deep learning